Petrichor and positionality: Occasion for a situated spatial epidemiology in the digital humanities - Walker, Blake (Geographical Research in the Digital Humanities. Spatial Concepts, Approaches and Methods, 2024)
Within months of the first COVID-19 outbreak in 2020, map-based dynamic platforms for disseminating population-level incidence, mortality, and later hospitalisation and vaccination data quickly grew to near total ubiquity (Rosenkrantz et al. 2021). As digital artefacts reproducing a reductionist factualisation (Kitchin et al. 2015) and statist sociopolitical anchoring (Everts 2020) of the pandemic, dashboards and interactive maps have featured prominently in public discourses of anxiety and othering as non-expert citizens sought to understand the pandemic as a sociocultural, political, and public health phenomenon, somehow manifest in spatial administrative units and spreading in shades of red as 'hotspots' emerged and dissipated. Simultaneously, these technologies have come to serve as a hybrid figurisation (Wilson 2009) of society's confrontation with geospatial and epidemiological methodologies and epistemologies, as rationalisations of the situation are contested via argumentations based on largely deterministic constructs such as hotspots, spatial and temporal lag, raw versus standardised rates versus case counts, covariates and confounding, and 'the curve'. The Digital Humanities concern themselves in part with reading the human condition through the digital artefacts we create and produce. Maps and geodata are among the many digital art forms that we can analyse through a Digital Humanities lens. In this disquisition, I draw primarily on critical GIScience perspectives grounded in the ongoing COVID-19 pandemic, presenting navigable inroads towards a more context-aware applied geostatistics, particularly in the context of spatial epidemiology. I argue that the increasing prominence of geostatistical concepts and their instrumentalisations for producing Lefebvrian space (Pierce & Martin 2015) underscore the need for a humanities-adjacent geostatistics that embraces the social, cultural, and situational, and optimistically suggest that amidst long-standing epistemological incongruencies (Schuurman 2000; Wilson 2017) stands a middle-ground between hermeneutic phenomenology and deterministic reductionism.
CRIS-Team Scopus Importer:2024-04-12
Keywords: COVID-19; Digital Humanities; Geographic Information Science; Health Geography; Spatial Epidemiology